Optimization of scratch resistance and mechanical properties in wollastonite‐reinforced polypropylene copolymers. (5th November 2015) - Sobhani, Hadi; Khorasani, Mohammad Mehdi
Abstract : The aim of this research was to establish a balance between scratch resistance and scratch damage visibility in the wollastonite‐filled heterophasic polypropylene copolymers.The influences of various factors including the surface hardness, elasticity, friction coefficient, and combinations thereof on the scratch behavior (scratch resistance and scratch visibility) were elucidated. Using micro‐scale and nano‐scale scratch tests and image analysis techniques, the scratch hardness, scratch depth, and scratch visibility of the composites were characterized.It was found that the introduction of wollastonite in the polypropylene copolymer matrix contributes to ductile fracture behavior because of an induced crystallization alteration. Accordingly, the scratch resistance of reinforced composites revealed an increase as a result of higher stiffness of the wollastonite as well as contribution of new crystalline structure. The addition of siloxane to the composites improved the resistance to surface damage by lowering the surface friction coefficient originated from enhanced chain mobility. Simultaneous addition of high density polyethylene and siloxane induced a significant influence on the resistance to the scratch damage. Copyright © 2015 John Wiley & Sons, Ltd.